Critical Challenges to Protecting Unaccompanied and Separated Foreign Children in the Western Cape: Lessons Learned at the University of Cape Town Refugee Rights Unit - Schreier, Tal (Refuge: Canada’s Journal on Refugees, 2013)
Despite South Africa having a relatively well developed legal and policy framework for securing the rights of children, there are a number of critical protection gaps that exist in terms of the implementation of these frameworks for unaccompanied or separated foreign children by magistrates, social workers and Department of Home Affairs’ officials in particular. This report focuses on the key challenges that the UCT Refugee Rights Unit has experienced in the protection of unaccompanied foreign children in the Western Cape province. In addition to setting out the legal and policy frameworks for dealing with foreign children in South Africa, the paper reviews some of the Unit’s cases and highlights various challenges in the course of undertaking this work. The key protection gaps that are highlighted include difficulties with or lack of suitable entry by foreign unaccompanied or separated children into South Africa’s child care and protection system, the unclear interface between the refugee regime and the child protection regime, inability to access legal documentation, and the poor level of knowledge of the legal and protection frameworks by government and frontline service providers.